2019
DOI: 10.3233/wor-192865
|View full text |Cite
|
Sign up to set email alerts
|

Occupational fatigue and mental health complaints among 8-hour shift workers of petrochemical industries in Iran

Abstract: BACKGROUND: Shift working is unavoidable in many industries with continual material processing such as petrochemical plants. So, the adverse effects of shift working on workers should be seriously considered. OBJECTIVE: This cross-sectional study evaluated occupational fatigue and mental health complaints and their relationship in rotating 8-hour shift workers. METHOD: In this study, 287 shift workers participated. The Multidimensional Fatigue Inventory (MFI-20) and General Health Questionnaire (GHQ-28) were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 31 publications
1
8
2
Order By: Relevance
“…These data are in line with the results of Watt et al [ 82 ] in the general Danish population without somatic disease. Although this level differs from that found by Bazazan et al [ 83 ] in a sample of petrochemical employees, these employees were subject to turnicity, working outside of regular hours.…”
Section: Discussioncontrasting
confidence: 78%
“…These data are in line with the results of Watt et al [ 82 ] in the general Danish population without somatic disease. Although this level differs from that found by Bazazan et al [ 83 ] in a sample of petrochemical employees, these employees were subject to turnicity, working outside of regular hours.…”
Section: Discussioncontrasting
confidence: 78%
“…The results of this study complement the results of previous studies, which reported that marital status, education level, years of service, and mental health status of workers are significantly related to chronic fatigue syndrome [25]. The opposite report showed no correlation between demographic characteristics (age, body mass index, marital status, education level, and shift work) and work-related factors in oil and gas industry workers in Iran [26] and Malaysia [27]. Work fatigue for female workers at Holland with a high education level had 44% higher odds of reporting high WRF when compared with women with a low or intermediate level of education [9].…”
Section: Demographic Factors and Wrfsupporting
confidence: 84%
“…Overall Fatigue. Ratings on Multidimensional Fatigue Inventory (MFI-20), which assesses five fatigue dimensionsgeneral fatigue, physical fatigue, reduced motivation, reduced activity, and mental fatigue, were reported to be high with shift workers (Bazazan et al, 2019;Bazazan et al, 2014;Rasoulzadeh et al, 2015). Two additional multidimensional fatigue surveys included the SOFI, which measures physical exertion, physical discomfort, lack of motivation, sleepiness, and lack of energy, and the Occupational Fatigue Exhaustion Recovery (OFER), which measures chronic fatigue, acute fatigue, and inter-shift recovery.…”
Section: Resultsmentioning
confidence: 99%